Marx-Type solid-state bipolar modulator topologies: Performance comparison - Canacsinh, Hiren (2015)
The operation of generalized Marx-type solid-state bipolar modulators is discussed and compared with simplified Marx-derived circuits, to evaluate their capability to deal with various load conditions. A comparative analysis on the number of switches per cell, fiber optic trigger count, losses, and switch hold-off voltages has been made. A circuit topology is obtained as a compromise in terms of operating performance, trigger simplicity, and switching losses. A five-stage laboratory prototype of this circuit has been assembled using 1200 V insulated gate bipolar transistors (IGBTs) and diodes, operating with 1000 V dc input voltage and 1 kHz frequency, giving 5 kV bipolar pulses, with 2.5 mu s pulse width and 5 mu s relaxation time into resistive, capacitive, and inductive loads.